Estimation of pastures on presence of Oribatidae population and their infection by Moniezia spp. larva - V. F. Nikitin; N. S. Dudka; P. A. Lemehov; A. V. Pljako (Российский паразитологический журнал, 2016)
Season dynamics of Oribatidae in the pastures and their infection by Moniezia spp. larva are investigated. The opportunity and expediency of realization of helminthological estimations of pastures at monieziosis and others anoplocephalatosis is established.